Enhancing Vocational Education: How Synergy between Program Management and Teacher Performance Drives Quality Learning - Fadhli, Fadhli; Komariah, Aan; Satori, Djaman; Marwan, Marwan; Salsabil, Syifa Hanifa; Permana, Riyaldi Dithia (Institut Agama Islam Negeri (IAIN) Curup, 2025)
Vocational High School (SMK) management differs significantly from that of Senior High Schools (SMA), particularly in managing technical programs and teacher responsibilities. This study investigates the effects of vocational program management and teacher performance on learning quality in public SMKs in Bireuen Regency, Aceh. Using a quantitative approach, data were collected via surveys from 176 teachers and analyzed using Structural Equation Modeling (SEM). Results show that both teacher performance and vocational program quality positively and significantly influence learning quality, with teacher performance also exerting an indirect effect. These findings underscore the importance of integrated program planning and teacher development to enhance student learning outcomes in vocational education. The study highlights the need for systemic alignment between program content and educator competencies to support the learning needs of SMK students. While focused on a specific regional context, the findings offer relevant insights for broader vocational education reform initiatives.